A micro perspective on political competition: Electoral availability in the European electorates - Aiko Wagner (Acta Politica, 2017)
This article develops an empirical measure of electoral availability, i.e., the micro perspective of political competition. As existing research conceptualizes political competition mainly as a macro- or party-level phenomenon, the micro perspective remains underdeveloped and, therefore, an important dimension of political competition, the availability of votes, is ignored. We introduce and discuss an individualized measure of electoral competition that is based on propensities to vote as indicators of the availability of voters to different political parties. The theoretical and empirical advantages of this measure are discussed: it is not restricted to parties' positions but is based on multidimensional party evaluations; it does not only focus on actual behavior but instead on the potential behavior of voters; the proposed measure takes all (relevant) parties into account instead of only including the two largest parties; as a continuous index it avoids arbitrary cut-off points; and the resulting individual-level results are easily summable to obtain party- and country-level values. Finally, correlations with individual, party and party system characteristics are discussed.
Additional information: This paper is part of a special issue of Acta Politica entitled `Information and Electoral Competition' edited by Sylvia Kritzinger, Susan Banducci, and Heiko Giebler.
Keywords: 330; electoral availability; political competition; competitiveness; European electorates